(untitled) (Research, Society and Development, 2021)
The present work emerges with the objective of presenting the construction of collaborative strategies involving Science Teaching with children in the face-to-face school return, marked by curriculum readaptation in COVID-19 pandemic times. It is motivated by the interest in developing issues involving the theme of health education, such as hygiene care. The methodological bias of this research is of a qualitative approach, of an applied nature and of the Action-Research type. Through the research, it was possible to think of playful strategies and experiments to develop pedagogical initiatives with the main stakeholders, the children, instigating curiosity, intervention, notes, dialogues and their perceptions, emphasizing the importance of attentive listening, listening to their machine questions. Thus, with the study, it was possible to sharpen the children’s narratives, tuning a present and attentive body to their notions about the coronavirus, with a view to producing possibilities for pedagogical exploration.